Visual agnosia. - Riddoch, M; Humphreys, G (2003)
As was originally proposed by Lissauer, visual recognition may break down either at an apperceptive or at an associative level. At an apperceptive level, finer grain distinctions may be made; the authors distinguished here between disorders of shape recognition and perceptual integration. It is not the case, however, that all patients with visual recognition deficits have impaired perception: poor recognition and naming may also result from damage to stored perceptual knowledge (e.g., structural descriptions), from problems in accessing semantic knowledge, from perceptual knowledge, or from impairments to semantic knowledge itself. These represent different types of associative deficit. In some cases, mild damage to stored perceptual knowledge also generates problems that are more severe on naming than on recognition and more severe for some categories of objects than others.